Toxic Effects of p-Cresyl sulfate and Indoxyl Sulfate on Bone : A Systematic Review - Mohammad Zulkarnaen, Ahmad Narihan; Dayang Erna Zulaikha, Awang Hamsin; Ahmad Faizal, Jelani; Gabriele Ruth Anisah, Froemming (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia., 2025)
Introduction: Chronic kidney disease (CKD) causes the accumulation of uremic toxins such as indoxyl sulfate (IS) and p-cresyl sulfate (pCS), leading to bone mineral disorders due to a dysfunction in the equilibrium between bone formation and resorption. Herein, we aimed to review and compile recent experimental and clinical studies that demonstrated the effect of pCS and IS on bone at the system, cellular, and molecular levels.Materials and methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria, a systematic review was performed using three electronic databases to appraise literature published between January 2005 to June 2023 on the effects of IS and pCS on bone. Results: Twenty-two relevant articles were included: 11 in vitro, 5 animal studies and 6 patient-based. IS and pCS induce toxic effects in bone cells by influencing cell viability, differentiation, proliferation, oxidative stress, and cell death, leading to bone morphometry alterations and low bone turnover. Higher doses of IS are needed to induce bone toxic effects compared to pCS. IS and pCS affect bone cells by upregulating sclerostin and decreasing levels of DMP-1, both vital for bone mineralization. Therapeutic interventions are available to reverse the toxic effects of IS and pCS on bone, namely probenecid, pravastatin, resveratrol and AST-120. IS and pCS also potentially serve as biomarkers for CKD-related bone diseases. Conclusion: The available evidence shows IS and pCS induce toxic effects on bone through various mechanisms. Further in-depth mechanistic studies are warranted to elucidate their underlying mechanisms in inducing bone changes.